The lettered knight : knowledge and aristocratic behavior in the twelfth and thirteenth centuries - Aurell, Martin (Central European University Press, 2016)
The encounter between knight and science could seem a paradox. It is nonetheless related with the intellectual Renaissance of Twelfth-Century, an essential movement for Western history. The knight is not only fighting in battles, but also moving in sophisticated courts. He is interested on Latin classics and reading, and even on his own poetry. He supports "jongleurs" and minstrels and he likes to have literary conversations with clerics, who try to reform his behaviour, which is often brutal. These lettered warriors, while improving they culture, learn how to repress their own violence and they are initiated to courtesy: selected language, measured gestures, elegance in dress, and manners at table. Their association with women, who are often learned, becomes more gallant. A mental revolution is acting among lay elites, who, in contact with clergy, use their weapons for common welfare. This new conduct is a sign of modernity